Ambiguous genitalia causing principle of utmost good faith in insurance agreements’ violation - Arofah, Syifa Nurul; Sabila, Firdausa; Luthfiyah, Annisa; Solichin, Solichin; Andri, Gusti Yosi (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to study the application of the principle of utmost good faith in ambiguous genitalia case studies in insurance agreements. The data collection technique is a literature study, aiming to draw conclusions on the application method of the principles of good faith. The results of the study confirmed that some insurance companies refuse to make an insurance agreement for individuals with gender ambiguity. Therefore, it is important to develop policies that are more inclusive and fair for all individuals, without exception.